Local diffusion indicators: a new tool for analysis of electrochemical mass transport - Elliott, JR; Compton, RG (Elsevier, 2022)
The recently introduced diffusion indicator (Haonan et al, J. Electroanal. Chem., 2019, 855, 113602) is generalised to characterise local mass transport fluxes to a non-uniformly accessible electrode to probe both qualitatively and quantitatively the nature of the diffusion to different parts of an electrode surface at different times following electrochemical perturbation. The approach is illustrated in respect of diffusion to a truncated sphere on a plane surface. The relative contributions of thin layer, linear and convergent diffusion following potential step chronoamperometry are evaluated. Comparison is made with analogous measurements on a micro-disc electrode. The results have implications for the transients accompanying the impact of nanoparticles on planar electrodes and for hanging mercury drop electrodes.